2014
DOI: 10.1128/jb.01760-14
|View full text |Cite
|
Sign up to set email alerts
|

Epoxide-Mediated Differential Packaging of Cif and Other Virulence Factors into Outer Membrane Vesicles

Abstract: Pseudomonas aeruginosa produces outer membrane vesicles (OMVs) that contain a number of secreted bacterial proteins, including phospholipases, alkaline phosphatase, and the CFTR inhibitory factor (Cif). Previously, Cif, an epoxide hydrolase, was shown to be regulated at the transcriptional level by epoxides, which serve as ligands of the repressor, CifR. Here, we tested whether epoxides have an effect on Cif levels in OMVs. We showed that growth of P. aeruginosa in the presence of specific epoxides but not a h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 54 publications
0
29
0
Order By: Relevance
“…We recently showed that P. aeruginosa secretes the CFTR inhibitory factor (Cif), an epoxide hydrolase that triggers the degradation of ABC transporter family members, including CFTR (4-8). Cif transcripts have been observed in sputum from patients with CF, and longitudinal studies of clinical isolates from individual patients confirm that P. aeruginosa maintains Cif expression for up to 15 y (7,9). Nonetheless, Cif's role in CF pathogenesis and the identity of possible host epoxide substrates have remained unclear.…”
mentioning
confidence: 99%
“…We recently showed that P. aeruginosa secretes the CFTR inhibitory factor (Cif), an epoxide hydrolase that triggers the degradation of ABC transporter family members, including CFTR (4-8). Cif transcripts have been observed in sputum from patients with CF, and longitudinal studies of clinical isolates from individual patients confirm that P. aeruginosa maintains Cif expression for up to 15 y (7,9). Nonetheless, Cif's role in CF pathogenesis and the identity of possible host epoxide substrates have remained unclear.…”
mentioning
confidence: 99%
“…These OMVs diffuse through overlying mucus and fuse with membrane lipid rafts, delivering virulence factors into the host cytoplasm. 30 OMVs are proinflammatory and cytotoxic to both the pulmonary and corneal epithelia. 31 The immune response to P. aeruginosa strains in the eye is dominated by dense neutrophil infiltrates forming neutrophil extracellular traps.…”
Section: Discussionmentioning
confidence: 99%
“…31 The immune response to P. aeruginosa strains in the eye is dominated by dense neutrophil infiltrates forming neutrophil extracellular traps. 30,31 Cytotoxic strains that are associated with higher rates of morbidity, including vision impairment, are able to evade this neutrophil capture mechanism by secreting high amounts of OMVs. 31 This mechanism suggests OMVs provide necessary factors for P. aeruginosa to establish corneal infection.…”
Section: Discussionmentioning
confidence: 99%
“…aeruginosa and OMV isolation. P. aeruginosa [strain PAO1 and clinical strain SMC1585 (23)] was grown overnight in lysogeny broth (LB) to an optical density of 1, and OMVs were isolated as described elsewhere in detail (3,(5)(6)(7)19). Briefly, overnight cultures of P. aeruginosa were centrifuged for 1 h at 3,500 rpm (4°C) to pellet bacteria.…”
Section: Methodsmentioning
confidence: 99%
“…P. aeruginosa secretes outer membrane vesicles (OMVs) that fuse with cholesterol-rich lipid rafts in the apical plasma membrane of airway epithelial cells and deliver many virulence factors, including Cif, into the cytoplasm, where it reduces wt-CFTR Cl Ϫ secretion (3,6,7,31,32). Cif enhances the ubiquitination and lysosomal degradation of wt-CFTR, thereby reducing CFTR Cl Ϫ secretion, mucociliary transport by airway epithelial cells, and the ability of mouse lungs to clear P. aeruginosa (18,31).…”
Section: Introductionmentioning
confidence: 99%